Enhancing Social Integration through Intra-ASEAN Travel - Gabriella Fardhiyanti; Victor Wee (JAS (Journal of ASEAN Studies), 2022)
The ASEAN Economic Community (AEC) was established in 2015 with the goal of enhancing regional integration, including social integration, which has been linked to the ASEAN populace's motivations for regional travel. This paper examines emerging intra-ASEAN travel using Esser's (2001) social integration dimension theory. To fully comprehend the vision of social integration and sustainable tourism development, continuous efforts must be made to develop, promote, and protect the member states' common interests through ASEAN integration. This study aims to assess whether the social integration dimension connects individuals in preference to travelling within the ASEAN region. A questionnaire survey of ASEAN nationality passengers at Malaysia's KLIA2 Airport was used to collect the data. The study findings will present social integration arising from intra-ASEAN travellers and the benefits of promoting tourism for economic stability in the region.